ANALISIS PENGUASAAN TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE (TPACK) OLEH GURU SMK PUSAT KEUNGGULAN KOTA MALANG - Maulana Paramaditya Ananta; Salsa Islam Lazuardini; Mari'atul Kamila Ramadhan (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
The Center of Excellence Vocational High School (SMK PK) program is designed to produce graduates with superior competence in their respective fields of expertise. This condition requires teachers to continuously improve the quality of the learning process they deliver. One important framework that can be utilized is TPACK, which refers to the integration of content knowledge (CK), pedagogical knowledge (PK), and technological knowledge (TK) in teaching and learning. This study aims to reveal the ability of SMK PK teachers to integrate these three aspects in order to support the development of competitive graduates. The research employed a qualitative method with a descriptive approach. Data were obtained from five productive subject teachers across different study programs in one SMK PK located in Malang City. The focus of the study was on teachers’ mastery of PCK, TCK, TPK, and TPACK domains in implementing learning activities. Data collection techniques included interviews, observations, and documentation. The findings indicate that in selecting instructional technology, teachers consider students’ characteristics and conditions while aligning them with predetermined learning outcomes. Teachers also tend to choose technological tools and representations that are more familiar and user-friendly to minimize potential difficulties.